The Effect of Betel Leaf Inhalation and Chest Physiotherapy on Airway Clearance in Children with Respiratory Tract Infections in the Purwodadi II Grobogan Community Health Center Area - Fitriani; Kusumaningrum, Yesita Ragil; Sugito, Bambang (INDOGENIUS, 2025)
Background & Objective: Acute Respiratory Infection (ARI) is a major public health problem as it remains one of the leading causes of mortality in developing countries. ARI continues to be the primary cause of morbidity and mortality from infectious diseases worldwide. Therefore, it is important to enhance mothers’ knowledge and attitudes regarding the definition, causes, signs and symptoms, prevention, and home care management of children with ARI. Improved understanding can encourage behavioral changes among mothers or families in preventing and managing ARI in children, thereby reducing its incidence. Non-pharmacological therapies such as betel leaf inhalation and chest physiotherapy are among the efforts that can help improve airway clearance in children with ARI. This study aimed to determine the effect of betel leaf inhalation therapy and chest physiotherapy on airway clearance among children with ARI in the working area of Purwodadi II Public Health Center, Grobogan Regency. Method: This research employed a quasi-experimental design with a two-group pre- test and post-test approach. The sample consisted of 30 children aged 5–12 years, divided into two groups: 15 children received betel leaf inhalation therapy, and 15 children received chest physiotherapy. Data were collected using an airway clearance observation sheet and analyzed using the Wilcoxon test. Result: The results showed a significant improvement in airway clearance after both betel leaf inhalation and chest physiotherapy interventions (p = 0.000 < 0.05). Conclusion: Betel leaf inhalation was effective in diluting mucus and facilitating sputum expectoration, while chest physiotherapy enhanced mucus mobilization through postural drainage, percussion, and vibration techniques.